Case report: Alternative approach for management of refractory volume overload in heart failure: usefulness of venous leg compression - Collado Macián, Carlos; Pujol Pocull, David; Dominguez, Fernando; López-Azor, Juan Carlos; Garcia-Pavia, Pablo; Nuñez, Julio; Cobo Marcos, Marta (Frontiers in Cardiovascular Medicine, 2023)
Background Management of patients with refractory congestion, is one of the most important challenges in the field of heart failure (HF). Diuretic therapy remains the most widely used therapy to achieve euvolemia. However, some patients experience fluid overload despite the use of high-dose diuretics and new strategies to overcome diuretic resistance are needed. Case Summary We report an 85 years-old male patient admitted for decompensated HF with persistent tissue fluid overload (peripheral edema) for more than two weeks despite high dose of intravenous furosemide with the combination of other diuretics. At this point, we performed leg venous compression using elastic bandages for three days. After 72 h, edema disappeared, and additional weight loss was achieved (1 kg/day). No side effects were observed and the patient was discharged home euvolemic. Conclusion Venous leg compression may be an alternative therapy in patients with persistent tissue fluid overload resistant to diuretics.